Identification on Residential Park Facilities Criteria Based on Visitor’s Perception - Achmad Ridwan Lubis; Dewi Septanti; Sarah Cahyadini (IPTEK Journal of Proceedings Series, 2020)
The soaring number of urban population and the rising of it from time to time will implicate on the pressure of the utilization of city spaces especially residential area, public and social facility also public open spaces in the city. The elevating development of residential area is not only causing the widening of built up land but also decreasing the availability of open spaces. In eastern Surabaya as one of the residential area development location has variety of activity in utilizing a housing scale of green open spaces. Furthermore, the efforts in optimizing parks around eastern Surabaya that can be used as public and social spaces. Citizen’s participation to fulfill those efforts are crucial as the perception influence the need of residential parks as a facility. Therefore, concept of providing facilities on the residential parks through the citizen’s perception needs to be acknowledge. The purpose of this research is to identify the criteria of facility on the parks based on the citizen’s perception. The step in this research, is to identify the residential park facility’s criteria based on the visitor’s perception. To find the answer, quantitative methods is used in this research. Descriptive statistic is used to answer the target of the research. According to the analysis’s results, the criteria of the preferred facility on the residential parks around eastern Surabaya with the highest frequency are trash bin, lights, park benches, shades, pedestrians’ side, children’s playground, public toilet, security guards’ post, easy accessibility, sports field, jogging track, vegetation’s variety and parking spots. Meanwhile, the non-preferred facilities are the ornament for the aesthetic like statues, water fountains, internet access, ready to drink water stations, signs, and gazebos.